Lubricants Inventory Control for Marine Port Maintenance - Chartniyom, Siradej; Ngamlerd, Jaruwan (Srinakharinwirot University Engineering Journal, 2020)
This article presents the development of the maintenance, repair & operating supplies (MRO) inventory system for the operation of an international portyard. Steps in the improvements focused on setting up suitable ordering and controlling methods to work as an integrated inventory approach. Firstly, ABC classification technique was used to prioritize 3 groups of lubricants according to their annual-usage levels. Subsequently, three controlling methods as 1) periodic review system, 2) Min-Max system and 3) a maintenance plan were considerd in setting a buying plan for the different groups. Finally, purchasing and controlling plans were released for the real operation of the sample port. The proposed approach results in the reduction of shortage in lubricants by 88.99%, and the reduction of the MRO inventory cost of 65,853 bahts, which implied 11.19% of annual usage value.